Peningkatan Pemahaman Siswa SMA Negeri 6 Pulau Enggano Melalui Edukasi Keuangan Dan Investasi Pasar Modal - Herpazah, Miskia; Mursalin, Supardi; Indra, Yetti Afrida (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2025)
The low level of financial literacy among Indonesians, particularly in remote areas such as Enggano Island, poses a significant challenge in fostering a financially literate generation capable of managing personal finances wisely. According to data from the Financial Services Authority (OJK), financial literacy in the capital market sector in 2016 was only 4.40%, with financial inclusion reaching just 1.25%. This condition highlights the urgent need for continuous educational interventions, especially for youth in underdeveloped regions. This community service project aimed to improve students’ understanding of basic financial and capital market investment concepts at SMA Negeri 6 Pulau Enggano. Implemented through a structured approach—including preparation, the delivery of a Level 1 Capital Market School (SPM), and evaluation using pre-test and post-test methods—the program recorded a significant improvement in students' comprehension. The average pre-test score of 6.7 increased to 12.75 in the post-test, with an N-Gain Score of 74.72%, indicating a high category of improvement. Challenges such as students' limited time and low initial understanding were addressed through interactive methods and contextual analogies. This initiative not only positively impacted students’ financial literacy but also served as a practical educational model for the 3T (Frontier, Outermost, Disadvantaged) regions. Recommendations from this activity include periodic replication of the program, involvement of financial institutions such as OJK and BEI, and integration of financial education into the school curriculum. Ultimately, the goal is to ensure equal access to financial literacy across all regions, including remote areas like Enggano Island.